2019
DOI: 10.24043/isj.88
|View full text |Cite
|
Sign up to set email alerts
|

Inequality of opportunity in an outermost region: the case of the Canary Islands

Abstract: This article estimates the inequality of opportunity (IO) for the Canary Islands archipelago, a European outermost region of seven islands, including two capital islands and five peripheral islands. To achieve this goal, a survey has been designed to cover a wide range of circumstances, including type of household, socioeconomic background, health status, type of school, family environment, and instilled values during childhood. This new database is one of the main contributions of the paper. For all of the Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Although policies are often decided by the national government, the analysis revealed that their implementation at the local level several thousand kilometres away was not easy. The ability to successfully adapt at the local level is a crucial element for ORs, as shown by Betancort et al (2019). The importance of this search for coherence and smart implementation at the local level to ensure the effectiveness of the policies deployed has also been emphasized by Rodriguez‐Pose and Vidal‐Bover (2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although policies are often decided by the national government, the analysis revealed that their implementation at the local level several thousand kilometres away was not easy. The ability to successfully adapt at the local level is a crucial element for ORs, as shown by Betancort et al (2019). The importance of this search for coherence and smart implementation at the local level to ensure the effectiveness of the policies deployed has also been emphasized by Rodriguez‐Pose and Vidal‐Bover (2022).…”
Section: Discussionmentioning
confidence: 99%
“…Inequalities are more marked there than elsewhere. Betancort et al (2019) noted that for the Canary Islands, there are many inequalities in terms of opportunities, both related to gender and education. This poverty is particularly linked to their insularity and isolation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Segundo, el presente estudio expande la investigación sobre el proyecto meritocrático en el caso español con un estudio empírico con base a una muestra representativa, y datos muy ricos, hasta hora poco explotados, aunque ya con buenas publicaciones disponibles (Cabrera Rodríguez et al, 2021) y que ha inspirado la creación de archivos de datos similares para entornos más específicos, como es el caso de las Islas Canarias (Betancort et al, 2019).…”
Section: Discusión Y Conclusiónunclassified
“…Although institutions in the archipelago are comparable to those in the rest of Spain. The islands have an income per inhabitant that is 82% of that in Spain, nearly the highest rates of unemployment (21.9%), youth unemployment (40.9%), long-term unemployment (38.1%) and relative poverty (35%), and the highest rate of the population at risk of social exclusion in the entire country with an AROPE (At Risk of poverty and/or exclusion) index of 44.6% in 2016 (Betancort, Darias, Marrero, Pérez, Rodríguez and Sánchez, 2019).…”
Section: Samplementioning
confidence: 99%